5/6y+1/5(y-6)=(y+1)/4

Simple and best practice solution for 5/6y+1/5(y-6)=(y+1)/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6y+1/5(y-6)=(y+1)/4 equation:


y in (-oo:+oo)

(1/5)*(y-6)+(5/6)*y = (y+1)/4 // - (y+1)/4

(1/5)*(y-6)-((y+1)/4)+(5/6)*y = 0

1/5*(y-6)+(-1*(y+1))/4+(5*y)/6 = 0

(1/5*4*6*(y-6))/(4*6)+(-1*6*(y+1))/(4*6)+(4*5*y)/(4*6) = 0

1/5*4*6*(y-6)-1*6*(y+1)+4*5*y = 0

20*y-6/5*y-174/5 = 0

94/5*y-174/5 = 0

(94/5*y-174/5)/(4*6) = 0

(94/5*y-174/5)/(4*6) = 0 // * 4*6

94/5*y-174/5 = 0

94/5*y-174/5 = 0 // + 174/5

94/5*y = 174/5 // : 94/5

y = 174/5/94/5

y = 87/47

y = 87/47

See similar equations:

| 3/5w=5w+22/25 | | 5x-4(4+5x)=13 | | -130=-6x-6x+2 | | 14x-3=12x+42 | | x^(4/3)-29x^(2/3)+100=0 | | 63/4x9 | | x/3+2-9/6+x/6-1 | | -5f-7+3.5=26.5 | | 6/7y+1/6(y-7)=y+1/7 | | 3x-5/10=7 | | 19+5/x=6 | | X+0.2x=24 | | 2y-3= | | 2.5(x+1)=1.5x | | 15.3=(-7.5k)+55.2 | | 0.7(6x+9)=3.4-(x-3) | | W/2.5=0.7 | | 2.33x+10+5.66x-9.5=12.5 | | 4x=8x+12x-16y | | M^2*m-30=0 | | 17(t-6)+4t=7(3t+4)-9 | | 2k^2-k-36= | | a/25=25 | | -5+8+-13= | | 2-4x=50 | | 0=x^4-29x^2-252 | | 2x-8+x=21 | | 2^(1/x)=0 | | 2^(1/x) | | 2/3x-2/3-2/5x+3/5-1 | | 2/x+3=5/2x+13/4 | | 7+3t-5=7t+10-3t |

Equations solver categories